Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem Based Learning di Sekolah Dasar - Raspita, Hanyyah; Eliyasni, Rifda (Universitas Negeri Padang, 2023)
AThe reason this study was conducted in the first place is that students' learning outcomes remain poor because the teacher has failed to direct students toward problems. The purpose of this study is to describe how integrated thematic learning with the Problem Based Learning (PBL) model improved learning outcomes in class V at SDN 18 Air Tawar Selatan, Padang City. By combining qualitative and quantitative methods, this study is classroom action research (CAR). This study was carried out over two cycles. The first cycle consisted of two meetings, while the second cycle consisted of one meeting with multiple stages—planning, executing, observing, and reflecting. 17 people, seven of whom were boys and ten of whom were girls, were the students of class V who served as the study's subjects. Tests, non-tests, and observation are all methods of data collection. This study's findings indicate an increase in: a) RPP cycle I received 88.5 percent (B) and cycle II received 94% (A); b) Teacher activities were implemented by cycle I with 83.5 percent (B) and 96% (A); c) Student activities were implemented by cycle I with 80% (C) and 91% (A); d) Student learning outcomes were assessed by cycle I with 76% (C) and 91% (A). The study's findings lead us to the conclusion that integrated thematic learning can benefit from the PBL learning model.